Analisis Keterampilan Membaca Permulaan Siswa Kelas I di SD Negeri 073 Jambur Padang Matinggi Kecamatan Panyabungan Utara Kabupaten Mandailing Natal - Nadia Riski; Nursyaidah Nursyaidah; Nashran Azizan (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
Reading is a cognitive process that involves understanding, retelling, and interpreting the meaning of written symbols. Beginning reading is the initial stage of learning to read, which can be developed through engaging activities involving letters, syllables, and simple words. This study was conducted to investigate the beginning reading skills of first-grade students at SD Negeri 073 Jambur Padang Matinggi, to identify the supporting and inhibiting factors, and to explore the efforts made to improve students’ reading abilities. This research employed a qualitative descriptive method with 16 students as subjects. Data were collected through observation and interviews with both teachers and students. The results showed that students’ beginning reading skills varied: 6 students were categorized as good, 6 as fair, and 4 as poor. The influencing factors were divided into internal and external aspects. Internal factors included a lack of interest and motivation to read, while external factors involved the school environment, family support, and learning strategies. Efforts to enhance reading skills included daily reading habits and consistent parental guidance. These findings highlight the importance of both internal and external support systems in the development of early reading skills among young learners.